STUDY OF PREVALENCE OF SCRUB TYPHUS IN ACUTE FEBRILE ILLNESS IN A TERTIARY CARE HOSPITAL, VISAKHAPATNAM - VANI , THAMMINA MEHER SRI SAI SUDHA (International Journal of Current Pharmaceutical Research, 2024)
Objective: Re-emergent cases of rickettsial disease, the scrub typhus is seen prevalent in cases of acute febrile illness. The objective of this study was to study the magnitude and prevalence of scrub typhus in a tertiary care hospital. Methods: This prospective study was carried on for a period of one year from February 2023 to February 2024. Inpatients between the age group of 16 to 25 y with a triad of fever for more than 5 d of onset with or without an eschar, headache, myalgia and abnormal haematological and biochemical parameters were included in the study. IgM ELISA for scrub typhus was performed. Results: Prevalence of scrub typhus in this study was 9.4% with higher male preponderance of 69.4% in 18 y age group 28.6%. Positive cases were recorded higher during post monsoon season of September 18.9%. Co-infection with dengue and malaria observed in 2 cases and ARDS was the complication in 3 cases. No mortality in this study. Conclusion: It is important to get familiar with the clinical and diagnostic laboratory findings of scrub typhus so as to differentiate it from other aetiologies of acute febrile illness.